WORK SAFETY ASPECTS USING A PARTICIPATORY ERGONOMIC APPROACH - Dian Palupi Restuputri; Moch Choirul Huda; Ahmad Mubin (Spektrum Industri, 2021)
The problem that we often encounter in the workplace is work accidents. It is fatal in work and frequently ignored by workers and company owners, especially small and medium enterprises. This study focuses on reducing the risk of work accidents through a participatory ergonomic approach. This method is a method in which all elements involved in the scope of work are invited to work together to solve existing problems. The result shows that the risk of MSDs is dangerous to the musculoskeletal system as the work posture resulted in a significant effect of tension. The physical work environment is not under existing standards. Lack of lighting can be fatal to workers, while too hot temperatures can affect worker comfort. The results of participatory ergonomics show that 85% of workers want a change in the physical work environment. The number of work accidents in batik centers after using a participatory ergonomic approach decreased and could increase work productivity by 11%.